2005
DOI: 10.1111/j.1525-139x.2005.00081.x
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of Temporary Hemodialysis Catheters to Permanent Hemodialysis Catheters: A Retrospective Study of Catheter Exchange versus Classic de novo Placement

Abstract: Many clinicians believe that de novo access is required when converting temporary hemodialysis (HD) catheters to long-term or permanent catheters. However, since vascular access sites are at a premium in the dialysis patient, it is important to preserve existing central venous catheters and conserve future access sites. In this retrospective study, data from 94 patients referred to interventional radiology for placement of long-term, tunneled HD catheters between July 2001 and September 2002 were reviewed. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
25
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 15 publications
3
25
0
Order By: Relevance
“…Therefore, overall infection risk due to this specific procedure reported by this study and other studies 8,[15][16][17] is similar to that of de novo catheter placement.…”
supporting
confidence: 53%
See 3 more Smart Citations
“…Therefore, overall infection risk due to this specific procedure reported by this study and other studies 8,[15][16][17] is similar to that of de novo catheter placement.…”
supporting
confidence: 53%
“…Other studies have reported similar infection rates, ranging from 1.0 to 1.1 infections/1,000 catheter-days. [13][14][15] Falk et al 16 have reported even higher 30-day infection incidence (9.4%) and rate (3/1,000 catheter-days). Recently, Bajaj et al 17 have…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Although in vitro testing has shown benefits with aerostatic sheath use, there are few clinical data investigating the risk of AE events during tunneled catheter placement with aerostatic sheaths (3,4). Additionally, over-the-wire exchange (OTWE) has become a standard of care in tunneled dialysis catheter (TDC) management as a means to preserve venous access, but little is known about the incidence of AE during OTWE (5)(6)(7)(8). The purpose of this study was to determine the effect of aerostatic sheaths on AE events during insertion of TDCs and to characterize such events during OTWE.…”
mentioning
confidence: 99%